MAMPUKAH KEPEMIMPINAN TRANSFORMASIONAL MENINGKATKAN MOTIVASI DAN KINERJA DI MASA ? - Astuty, Isthofaina (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
Changes in conditions caused by the Covid-19 pandemic have forced all levels of the business sector to adapt. This situation requires more optimal employee performance, both in quality and quantity so that it will have a positive impact on the company. There are several causes that affect employee performance, including transformational leadership style and work motivation. Transformational leadership style is good for use in companies that want change for the better. Likewise with motivation, when the work motivation of employees is strong, the urge to work with quality will be realized. Therefore, this study aims to measure the effect of transformational leadership and work motivation on employee performance at one of the companies PT. Astra Agro Lestari, Tbk which is engaged in the national plantation sector. The research uses online data collection methods. Data were analyzed using path analysis with regression. The data is processed using regression analysis and reinforced with Sobel to predict the influence between the independent variables in the form of leadership style and work motivation with the dependent variable which is employee performance. The results of this study indicate that leadership style affects motivation but does not affect performance, and motivation affects employee performance. Furthermore, the results of the Sobel test show that leadership style has a positive effect on employee performance through employee motivation.